Strategic planning of prevention and surveillance for emerging diseases and invasive species - Jue Wang; Brenda J. Hanley; Noelle E. Thompson; Yu Gong; Daniel P. Walsh; Carlos Gonzalez-Crespo; Yitong Huang; James G. Booth; Joe N. Caudell; Landon A. Miller; Krysten L. Schuler (Proceedings of the National Academy of Sciences, 2025)
Emerging infectious diseases and biological invasions pose increasing threats to public and ecosystems health. Proactive measures—such as prevention and surveillance taken before initial detection of the pathogen or species—are essential to ensure minimal spread prior to first detection. We developed an optimization model to determine where, when, and how much effort should be allocated to prevention versus surveillance. The model accounts for imperfect detection, system dynamics, spatial heterogeneity in risk and costs and is scalable to large landscapes. We found that the most cost-effective strategy is to maintain the prevention and surveillance efforts at stable equilibrium for the majority of the time, with deviations occurring only initially to steer the system toward the equilibrium. The equilibrium effort is jointly determined by the introduction risk, management costs, and total budget. Application of this model to chronic wasting disease in New York State suggests that the optimal strategy could reduce the cumulative disease cases before initial detection by an average of 22% compared to current practice. The optimal surveillance strategy could detect the disease on average over 8 mo earlier than the current strategy.